Removal of organics from treated palm oil mill effluent (POME) using powdered activated carbon (PAC) - Muyibi, Suleyman Aremu; Tajari, Tamrin; Jami, Mohammed Saedi; Amosa, Mutiu K. (2013)
In 2011, Malaysia produced more than 16 million tonne of crude palm oil (CPO) with almost 93 million tonne of fresh fruit bunches (FFB) processed. This large amount of FFB processed required very huge amount of water for crude oil extraction which later produced millions tonne of wastewater as palm oil mill effluent (POME). Millions of tons of treated POME are discharged into the water bodies in Malaysia as ‘clean’ waste after anaerobic-aerobic treatment. However, treated POME potentially can become alternative water resource for reclamation and reuse on-site either for plant cleaning or as feed water process. The removal of organics like chemical oxygen demand (COD) and total suspended solids (TSS) in treated POME were studied using commercial powdered activated carbon (PAC) as adsorbent. It shows that the COD and TSS removal were increase as the PAC dosage increases before both reach equilibrium at dosage 2 g. The COD adsorption was best suit with the Freundlich isotherm model and the isotherm model for TSS was suit the Langmuir isotherm with R2 values 0.9742 and 0.9782 respectively.